2019
DOI: 10.1039/c9ra07943b
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and regeneration of leaf-based biochar for p-nitrophenol adsorption from aqueous solution

Abstract: As an environmentally friendly and low-cost adsorbent, biochar has great potential in wastewater treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 57 publications
1
18
0
Order By: Relevance
“…For example, the Fe oxides NPs-supported biochar derived from leaves showed efficient removal ability for Cr(VI) and As(V) (Liang et al 2019c;Sahu et al 2019). Pristine or modified biochar derived from leaves also acted as an excellent adsorbent for organic pollutants (Hu et al 2019;Ma et al 2019;Vyavahare et al 2019). Additionally, leaves-derived biochar could serve as a promising soil conditioner to increase agricultural productivity (Konaka et al 2019).…”
Section: Biochar Productionmentioning
confidence: 99%
“…For example, the Fe oxides NPs-supported biochar derived from leaves showed efficient removal ability for Cr(VI) and As(V) (Liang et al 2019c;Sahu et al 2019). Pristine or modified biochar derived from leaves also acted as an excellent adsorbent for organic pollutants (Hu et al 2019;Ma et al 2019;Vyavahare et al 2019). Additionally, leaves-derived biochar could serve as a promising soil conditioner to increase agricultural productivity (Konaka et al 2019).…”
Section: Biochar Productionmentioning
confidence: 99%
“…For example, Zhang et al found a good adsorption capacity for 4-nitrophenol in the magnetite that was modified with tetraethoxysilane and vinyltriethoxysilane (Zhang et al 2019). Ma et al (2019) used biocarbon prepared from leaves of Platycladus Orientalis as absorbent for 4-nitrophenol, where a maximum adsorption capacity of 622.73 mg/g (at 298 K) was reported. Meng et al used N-isopropylacrylamide as a functional monomer, which was grafted on cyclodextrin/azobenzene to prepare a light-responsive adsorbent for 4-nitrophenol.…”
Section: Introductionmentioning
confidence: 99%
“…24 In addition, a large number of studies have used ZnCl 2 as activating agent of the carbon precursor. [25][26][27] Zinc chloride activation method gives activated carbon extremely high specic surface area and pore volume.…”
Section: Introductionmentioning
confidence: 99%